Activities of daily living questionnaire from patients' perspectives in Parkinson's disease: a cross-sectional study. Issue 1 (December 2016) - Lee, Su-Yun; Kim, Sung; Cheon, Sang-Myung; Seo, Jung-Wook; Kim, Min; Kim, Jae
Abstract Background The aim of this study was to develop an assessment tool for activities of daily living (ADL) from the perspective of patients with Parkinson's disease (PD) and examine the validity and reliability of the assessment. Methods A preliminary 45-item questionnaire was developed through intensive interviews with 54 patients with PD and administered to another group of 248 patients with PD. Based on clinical and statistical analyses, 20 ADL-items were selected. The final 20-item questionnaire was examined in the other group of 59 patients with PD. Results The new ADL questionnaire showed high internal consistency (Cronbach's α, 0.962–0.966) and acceptable test-retest reliability (0.632–0.984). Concurrent validity was shown as a significant positive correlation between the new ADL questionnaire and other ADL or clinical instruments. The Hoehn and Yahr stage showed the highest degree of correlation with the new ADL questionnaire, followed by the other ADL scales (Schwab and England ADL and the ADL subscore of the Unified Parkinson's Disease Rating Scale). Additionally, a regression analysis was conducted with the disease-specific quality of life questionnaire, and the new ADL questionnaire was the most powerful predictor of quality of life among the clinical instruments. Conclusions The new ADL questionnaire is a valid tool for assessing ADL from the perspectives of patients with PD.